Acceleration of electrons in hollow glass capillaries under the action of intense picosecond laser pulses. (September 2021) - Flegentov, V A; Safronov, K V; Gavrilov, D S; Kakshin, A G; Pkhaiko, N A; Potapov, A V
Abstract: The generation of relativistic electron beams in hollow glass capillaries is investigated using a picosecond laser system. A plasma is formed in a capillary due to the ablation of its inner walls by a specially formed pre-pulse. Electron beams with an opening angle of ≈40 mrad, exponential energy spectrum with maximum energy about 20 MeV, and a total charge of ≈0.2 nC are experimentally detected.